Nossidium katyae, a new species of Bolivian Ptiliidae (Coleoptera), described and figured - Darby, Michael (Zootaxa, 2015)
This is the third report on a collection of Ptiliidae from Bolivian forest leaf litter made by Dr Petr Baňař of the Brno Museum (Czech Republic) in 2013. A new species Nossidium katyae, is described and figured on the basis of a single specimen collected in the Amboro National Park. Comparative figures of Nossidium pilosellum Marsham are provided together with a brief synopsis of views on the desirability of establishing a new subfamily within the Ptiliidae to include Nossidium group species.